Hello avatar : rise of the networked generation - Coleman, Beth (The MIT Press, 2011)
An examination of our many modes of online identity and how we live on the continuum between the virtual and the real.Hello Avatar!Or, {llSay(0, "Hello, Avatar!"); is a tiny piece of user-friendly code that allows us to program our virtual selves.In Hello Avatar , B.